EUROPEAN BORDER AND COAST GUARD STANDING CORPS CATEGORY 1 BASIC TRAINING TOPICALITIES IN ENSURING THE EU BORDER SECURITY - Frankowska, Iwona (Border Security and Management, 2023)
Establishment of the European Border and Coast Guard Standing Corps Category 1 has been recently the most visible change in the European approach in the management of the EU external borders. The political decision of the EU to have its own law enforcement officers for border protection and migration management and return-related tasks, has manifested a paradigm shift, also in training and education. The European Border and Coast Guard Agency (Frontex) has a leading role in capacity building, for example in terms of providing training for the members of the Category 1. The Agency Regulation provides a legal basis for the statutory staff of the Standing Corps, in particular highlighting the importance of training based on common values and culture, and respect of fundamental rights. The European dimension of the Standing Corps training is underpinned by the legal and ethical responsibilities of the Agency to ensure that the members of the Standing Corps are well trained and fully prepared to perform tasks with executive powers. The main aim of the paper is to explore the establishment of standing corps from the perspective of basic training. The context presented supports the thesis that the initial training serves as the foundation of public agreement and investment for common safety and security. The paper builds upon hands-on experience of the author and draws the general conclusion to prove the thesis based on the legal instruments presented and implementation of basic training editions.